1981
DOI: 10.1021/bi00512a033
|View full text |Cite
|
Sign up to set email alerts
|

Light-scattering investigation of the subunit dissociation of Homarus americanus hemocyanin. Effects of salts and ureas

Abstract: The subunit dissociation of the hemocyanin of the lobster, Homarus americanus, by the various salts of the Hofmeister series and the hydrophobic reagents of the urea-guanidinium chloride (GdmCl) class was investigated by laser light scattering molecular weight measurements. The dissociations of the hemocyanin dodecamers to hexamers by the various salts and the lower members of the urea series are found to be rapid and reversible, as predicted by the mass action law for monomer-dimer type of reactions. The salt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 34 publications
4
29
0
Order By: Relevance
“…* where RB is the measured Rayleigh ratio, K' is the lightscattering constant, and B'is the nonideality or second virial coefficient taken as 1 X lo-* L.mol.g-2 (Herskovits et al, 1981b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…* where RB is the measured Rayleigh ratio, K' is the lightscattering constant, and B'is the nonideality or second virial coefficient taken as 1 X lo-* L.mol.g-2 (Herskovits et al, 1981b).…”
Section: Resultsmentioning
confidence: 99%
“…The few hemocyanins that have been found that appear to be homogeneous or show only moderate effects of subunit heterogeneity are those of the isopods Ligia exotica and Bathynomus giganteus (Terwilliger et al, 1979;Van Holde & Brenowitz, 1981) and the lobster Homarus americanus (Morimoto & Kegeles, 1971; Herskovits et a]., 1981b). The association-dissociation behavior of the latter dodecameric protein to hexamers was found to be rapid and reversible, with the concentration dependence of the molecular weight correctly predicted by the law of mass action (Morimoto & Kegeles, 1971;Herskovits et al, 1981b).…”
mentioning
confidence: 80%
“…Figure 2 shows the relative populations of the different aggregation states of the molecule according to their dependence on pH (A) and on Ca +2 concentration (B). Differently from all the known similar systems (Siezen & Van Driel, 1974;Zolla et al, 1978;Bonaventura & Bonaventura, 1980;Van Holde & Brenowits, 1981;Van Holde & Miller, 1982;Brunori et al, 1985;Herskovits et a/., 1981), the '60 S species, i.e. the state of maximum aggregation, rapidly disappears in the presence of 10 mM CaCl 2 at pH values higher than 6.5, and an intermediate aggregation state (30 S) is stabilized.…”
Section: Subunit Associationmentioning
confidence: 76%
“…particles. The measured intensity correlation function G (2) (τ ) can be related to the field correlation function G (1) (τ ) via the Siegert relation (2) .…”
Section: Static and Dynamic Light Scatteringmentioning
confidence: 99%
“…Two hexamers built up the dodecameric hemocyanin of Homarus americanus. At physiological pH and ionic conditions, the dodecamer with a molecular weight of 940 kDa (estimated by ultracentrifugation) is the dominant species of the hemocyanin of H. americanus [1][2][3]. Dissociation studies were performed by means of urea, guanidinium chloride and salts of the Hofmeister series.…”
Section: Introductionmentioning
confidence: 99%